Implementation of infection control in health facilities in Arua district, Uganda: a cross-sectional study - Wasswa, Peter; Nalwadda, Christine K.; Buregyeya, Esther; Gitta, Sheba N.; Anguzu, Patrick; Nuwaha, Fred (BMC infectious Diseases, 2015)
At least 1.4 million people are affected globally by nosocomial infections at any one time, the vast majority of these occurring in low-income countries. Most of these infections can be prevented by adopting inexpensive infection prevention and control measures such as hand washing. We assessed the implementation of infection control in health facilities and determined predictors of hand washing among healthcare workers (HCWs) in Arua district, Uganda. We interviewed 202 HCWs that included 186 randomly selected and 16 purposively selected key informants in this cross-sectional study. We also conducted observations in 32 health facilities for compliance with infection control measures and availability of relevant supplies for their implementation. Quantitative data underwent descriptive analysis and multiple logistic regressions at 95 % confidence interval while qualitative data was coded and thematically analysed. Most respondents (95/186, 51 %) were aware of at least six of the eight major infection control measures assessed. Most facilities (93.8 %, 30/32) lacked infection control committees and adequate supplies or equipment for infection control. Respondents were more likely to wash their hands if they had prior training on infection control (AOR = 2.71, 95 % CI: 1.03–7.16), had obtained at least 11 years of formal education (AOR = 3.30, 95 % CI: 1.44–7.54) and had reported to have acquired a nosocomial infection (AOR = 2.84, 95 % CI: 1.03–7.84). Healthcare workers are more likely to wash their hands if they have ever suffered from a nosocomial infection, received in-service training on infection control, were educated beyond ordinary level, or knew hand washing as one of the infection control measures. The Uganda Ministry of Health should provide regular in-service training in infection control measures and adequate necessary materials.
Keywords: Healthcare workers; Infection control; Implementation; Hand washing; Health facilities